Ferroelectric and dielectric characterization studies on relaxor- and ferroelectric-like strontium-barium niobates - Matyjasek, K.; Dec, J.; Miga, S.; Łukasiewicz, T. (Condensed Matter Physics, 2013)
Ferroelectric domain structure evolution induced by an external electric field was investigated by means of nematic liquid crystal (NLC) method in two strontium-barium niobate single crystals of nominal composition: Sr₀.₇₀Ba₀.3₀Nb₂O₆ (SBN:70 - relaxor) and Sr₀.₆a₀.₇₄Nb₂O₆ (SBN:26 - ferroelectric). Our results provide evidence that the broad phase transition and frequency dispersion that are exhibited in SBN:70 crystal have a strong link to the configuration of ferroelectric microdomains. The large leakage current revealed in SBN:26 may compensate internal charges acting as pinning centers for domain walls, which gives rise to a less restricted domain growth similar to that observed in classical ferroelectrics. Microscale studies of a switching process in conjunction with electrical measurements allowed us to establish a relationship between local properties of the domain dynamics and macroscopic response i.e., polarization hysteresis loop and dielectric properties. Еволюцiя сегнетоелектричної доменної структури, iндукованої зовнiшнiм електричним полем дослiджу-валась за допомогою методу нематичного рiдкого кристалу в двох монокристалах стронцiй-барiєвого нiобату номiнального складу: Sr₀.₇₀Ba₀.3₀Nb₂O₆ (SBN:70 — релаксорний) i Sr₀.₆a₀.₇₄Nb₂O₆ (SBN:26 — сегнетоелектричний). Нашi результати показують, що широкий фазовий перехiд i частотна дисперсiя, продемонстрованi кристалом SBN:70, мають тiсний зв’язок iз конфiгурацiєю сегнетоелектричних мiкро-доменiв. Великий струм стiкання, виявлений в SBN:26, може компенсувати внутрiшнi заряди, що дiють як центри пiнiнгу для доменних стiнок, що приводить до менш обмеженого росту доменiв подiбно до того, що спостерiгається в класичних сегнетоелектриках. Мiкромасштiбнi дослiдження процесу перемикання в поєднаннi з електричними вимiрюваннями дозволяють встановити спiввiдношення мiж локальними властивостями динамiки доменiв i макроскопiчним вiдгуком, а саме, гiстерезисною петлею поляризацiї i дiелектричними властивостями.